O desacoplamento do núcleo supraquiasmático altera o fenótipo da porção ventrolateral na fase escura na dessincronização forçada - Tamires Amorim Marinho (2023)
In mammals, the suprachiasmatic nucleus (SCN) of the hypothalamus is the central circadian oscillator or "clock." Mainly, SCN synchronizes the circadian rhythms to the light-dark (LD) cycle, and it generates rhythms under constant dark conditions. Exposure to symmetrical LD cycles with a period (T) of 22 h (11:11h) leads to the dissociation of the SCN into two oscillators. One oscillator located in the ventrolateral (vl) portion of the nucleus remains synchronized to the LD cycle, while the other, present in the dorsomedial (dm) portion, remains synchronized to the animal's endogenous rhythm (tau, t), typically with t > 24 hours. Although the impact of this protocol on SCN-regulated rhythms is well-characterized, its specific effect on SCN physiology is not fully understood. Therefore, the objective of this study was to characterize the effect of forced desynchronization on the expression of key neuropeptides in each SCN portion, namely, vasoactive intestinal polypeptide (VIP) and vasopressin (AVP), which are highly expressed in the vl- and dm-SCN, respectively, as well as on SCN neuronal activity assessed through immunohistochemistry of the Fos-related antigens (abbreviated as c-Fos) immediate early gene family. For this purpose, Wistar rats were subjected to symmetric light regimes of 12h light:12h dark [Control group (T24)] or 11:11h light:dark [Desynchronized (T22) group]. Telemetric recordings were conducted in both groups to analyze spontaneous locomotor activity (SLA) and core body temperature (Tc) rhythms. After 10-15 days, the animals were transcardially perfused at zeitgeber times (ZTs) 2, 8, 14, and 20, and the expression of VIP, AVP, and c-Fos was evaluated through immunohistochemistry. Quantification was performed by counting immunoreactive (ir) cells in each SCN portion. As a result of forced desynchronization, SLA and Tc rhythms exhibited two significant periods, one around 22 h and another >24 h, but with lower robustness, mesor, and amplitude compared to the Control group (T24). Desynchronization did not alter the number of AVP-ir cells at different ZTs, but it abolished the temporal variation in VIP expression. Furthermore, unlike the T24 animals, the number of c-Fos-ir neurons in the vlSCN increased at ZT20 (dark phase) compared to other ZTs in the T22 animals. The SLA rhythm in the Desynchronized group (T22) showed a negative correlation with the number of AVP-ir neurons and c-Fos-ir neurons in the dmSCN. In contrast, the positive correlation observed in the Control group (T24) between VIP-ir and AVP-ir was lost in the Desynchronized (T22) animals. The number of VIP-ir neurons and c-Fos-ir neurons in the vlSCN of Desynchronized (T22) animals at rest during the dark phase (misaligned) was lower than that of T22 animals in activity during the dark phase (aligned). Thus, the forced desynchronization protocol alters the neuronal activity profile of the vlSCN and the expression of VIP in the SCN while maintaining the neuronal activity profile of the dmSCN and the temporal expression of AVP.